Analyse exploratoire d’un instrument d’évaluation des compétences professionnelles à l’enseignement en contexte de stage au préscolaire et au primaire - Blouin, Martin; Marzouk, Abdellah; Dion, Alexandra (Canadian Journal of Education/Revue canadienne de l’éducation, 2025)
The Reference Framework for Professional Competencies for Teachers serves as the foundation for the professional development of interns in teaching programs. The update of this framework (MEQ, 2020) required the revision of the assessment tools used in internship settings to ensure their alignment with the new development axes proposed by the ministry. As part of this project, we present the results of a consultation conducted with 42 associate teachers and supervisors, aimed at assessing the clarity and validity of an assessment tool implemented during a first-year internship in the preschool education and primary teaching program. The results show that, in general, the tool contains clear statements and allows for a fair evaluation of the full range of competencies suggested by the updated version of the competency framework.